Photoproducts Formation from Salicylic Acid and Poly(allylamine hydrochloride) in Aqueous Solution Induced by UV-B Radiation - Romario J. da Silva; Nara C. de Souza; Josmary R. Silva (Advances in Condensed Matter Physics)
We report on the investigation of the influence of UV-B radiation (306 nm) on the salicylic acid mixed with poly(allylamine hydrochloride), PAH, in aqueous solution. UV-Vis spectra versus irradiation time reveal kinetics of photoproducts formation. At pH 9 and 10 are found a growth regime and another of decay of photoproducts formation. In addition, the growth does not depend on temperature, whereas the decay showed a significant dependence on this parameter suggesting a thermally activated process. These processes were well fitted with first-order exponential functions.